PERAN DAN POSISI PUBLIC RELATIONS DALAM HOSPITALITY INDUSTRY - Tandiyo Pradekso; Yanuar Luqman; Taufik Suprihatini (Faculty of Social and Political Sciences, Universitas Diponegoro, 2013)
The role of public relations in hospitality industry had been significantly increasing along with the rapid growth of the industry. A study of the issue in 2 respective hospitals and a hotel indicates that each had set a different level of position within the management. Regardless to the type of the organization, public relations with the higher level of position had a better access to resources and decision making, which consecutively put them as expert prescriber. Converssely, a stumpy management value had dispose public relations as a merely communication techni cian. Organizational culture and communication climate were considered as determinants to how the management perceives public relations.